Effects of self-monitoring on math competency of an elementary student with cerebral palsy in an inclusive classroom. Issue 3 (3rd July 2017) - Sheehey, Patricia H.; Wells, Jenny C.; Rowe, Mary
ABSTRACT: Students with cerebral palsy (CP) without severe intellectual impairments often experience difficulties in mathematics performance. Given the high prevalence of learning difficulties in students with CP, few studies have examined interventions to improve the math competency of these students (Jenks et al., 2009 ). A single-subject reversal design was used to examine the impact of a tactile cued self-monitoring with self-graphing intervention on the number of basic math problems completed and the number of math problems completed accurately by a student with CP in a first-grade inclusion classroom. Results indicated that the student increased the number and accuracy of single-digit addition and subtraction computations during independent work in an inclusion setting using this intervention.